Water quality evaluation for cattle consumption in Santa Fe, Argentina - Boglione, Rosana (2025)
[Introduction]: Water is essential for all living beings as it facilitates nutrient transfer, waste elimination, and body temperature regulation. Groundwater is the primary source for bovine livestock consumption, and poor-quality water can negatively affect their health, reproduction, and productivity. In Argentina, bovine farming for meat and milk production is a significant economic activity, making it crucial to ensure an adequate supply of water in both quantity and quality. [Objective]: This study aims to evaluate groundwater quality for cattle in the Santa Fe dairy basin, Argentina, using a water quality index adapted for bovines. [Methodology]: During the 2023-2024 period, groundwater samples were collected from one of the main dairy basins in the country. Parameters significant to water quality for bovine consumption, such as pH, Total Dissolved Solids, Sulfate, Chloride, Nitrate, and Arsenic, were analyzed at each monitored well. Each parameter was assigned a score based on its harmful effects on livestock, and a mathematical equation was applied to classify water quality from very good to extremely poor. [Results]: The study revealed that a high percentage of samples in the dairy basin are of good or very good quality, although wells with poor water quality were also identified. [Conclusions]: The findings highlight the importance of monitoring and managing groundwater quality to ensure sustainable bovine farming in the Santa Fe dairy basin.